Adaptation of Retail Fuel Prices to International Crude Oil Changes and Cartel Formation: The Case of Cyprus - Constantinou, Constantinos (2013)
This study primary aims in investigating the responses of fuel prices to changes in international prices of oil for the market of Cyprus. Fuel pricing constitutes a concern of public debates for several periods. Similar to other countries, the dramatic historical increases in retail fuel prices have rose suspicions and consumers often complain that responses to crude oil changes are asymmetric. An asymmetric error correction model on weekly price changes for the years 2005–2011 was utilized. First, an examination of the price response mechanism in the European market has been conducted. Estimates signify considerable variations in the adjustment mechanism across EU countries. Empirical evidences for Cyprus show week evidences of asymmetric response. Secondly, an empirical analysis on company based data with the utilization of an Error Correction Model and a Threshold Error Correction Model was carried out for investigating the firms reactions to crude oil prices. Again, the evidences are week and cannot justify the existence of collusive behaviour among retailers.